Quorum Sensing, Biofilm, and Intestinal Mucosal Barrier: Involvement the Role of Probiotic - Deng, Zhaoxi; Luo, Xin M.; Liu, Jianxin; Wang, Haifeng (Frontiers in Cellular and Infection Microbiology, 2020)
The intestine is a particularly dynamic environment in which the host constantly interacts with trillions of symbiotic bacteria called the microbiota. Using quorum sensing (QS) communication, bacteria can coordinate their social behavior and influence host cell activities in a noninvasive manner. Nowadays, a large amount of research has greatly spurred the understanding of how bacterial QS communication regulates bacterial cooperative behaviors due to coexistence and host-microbe interactions. In this review, we discuss bacterial QS in the gut and its role in biofilm formation. As a biological barrier, the mucosal immune system can effectively prevent pathogenic microorganisms and other immunogenic components from entering the internal environment of the host. We focus on the relationship between biofilm and intestinal mucosal immunity, and how probiotic bacteria may regulate them. This review is to provide a theoretical basis for the development of new techniques including probiotics targeting the intestinal barrier function, thereby improving gut health.